Estudio técnico productivo del café ecológico en la asociación de artesanos El Colmenar en la parroquia San Antonio de las Aradas del cantón Quilanga, provincia de Loja - Castillo Calva, Manuel Florencio (2016)
The present research work entitled "PRODUCTIVE TECHNICAL STUDY OF ECOLOGICAL CAFÉ IN THE ASSOCIATION OF ARTISANS THE COLMENAR IN THE PARK OF SAN ANTONIO DE LAS ARADAS DEL CANTÓN QUILANGA, PROVINCE OF LOJA" was held in the parish of San Antonio de las Aradas, Cantón Quilanga, the following objectives were proposed: to carry out a diagnosis of coffee production, to prepare a technical guide for coffee cultivation and to socialize the results of the research with the producers of the sector. The methods used for the development of the present investigation were: the inductive, deductive, analytical, scientific, bibliographic, explanatory method through the application of techniques such as documentary collection, direct observation and surveys, in this way it was possible to know the deficiencies and opportunities In the cultivation of organic coffee, and through the information collected the necessary data were obtained for the determination of said study, its study variables are as follows: total hectares available, number of hectares destined to the coffee crop. Age of planting , Pests and diseases, yield per hectare, Production costs, production income, profitability The results obtained in our research show that there is a pest and disease infestation of coffee cultivation, in view of this situation an ecological technical manual is foreseen for its preventive control through the technical guidance we have proposed for the improvement of the coffee farms of The area, which will help inform farmers about the technical management of organic coffee Currently in the area of Quilanga has new varieties of coffee with a high level of production and resistance to rust, yields are currently low (2.5 quintals per hectare), production costs per hectare are moderate (9738 USD), Production income is USD 839.85, giving a profitability of 26%, on average per producer in a Ha. It is concluded that coffee production in the study sector is producing an average of 2.5 quintals per hectare, which are below the national production levels corresponding to 6 quintals per hectare, according to sources (MAGAP 2016). However, this yield is due to the fact that the plantations are young and the production levels per hectare can be increased with the application of technical management of the coffee crop. Therefore, it is recommended to follow the rules established in the production management guide for coffee, which will increase the profitability of production per hectare.